Indices of the State of Monocyte-Phagocyte System Cells as the Characteristics of the Change in Total Immune Reactivity of an Organism after Application of the Products of Embryofetoplacental complex - Rassokha, I. V.; Goltsev, A. N.; Ostankova, L. V.; Mikhalin, M. A. (Problems of Cryobiology and Cryomedicine, 2002)
The change in structural and functional organisation of cells of monocyte-phagocyte system (MPhS) during adjuvant arthritis (AA) has been studied. There was proposed the possibility to apply the products of embryofetoplacental complex (PEFPC) capable of changing the state of immune competent sphere.